2007
DOI: 10.1021/jp067672h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lasing Properties of Dissymmetric Eu(III) Complex with Bidentate Phosphine Ligands

Abstract: The luminescent and lasing properties of Eu(III) complexes were enhanced by using an dissymmetric Eu(III) complex. The photophysical properties (the emission spectral shapes, the emission lifetimes, the emission quantum yields, and the stimulated emission cross section (SEC)) were found to be dependent on the geometrical structures of Eu(III) complexes. The geometrical structures of Eu(III) complexes were determined by X-ray single crystal analyses. The symmetrical group of Eu(hfa)3(BIPHEPO) (tris(hexafluoroac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
81
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 79 publications
8
81
0
1
Order By: Relevance
“…The single-crystal structural measurements of 1-3 were performed on a Rigaku R-AXIS SPIDER IP diffractometer with graphite monochromated Mo Kα radiation (λ= 0.71073 Å) at 296 K. Crystal data [25] for [Tb(dbm) 3 (14), which indicates that the absolute configurations of 3 can be determined. The crystal data for 1 and 2 are almost the same as the literature [24] .…”
Section: X-ray Crystallography Of Chiral Ln(iii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The single-crystal structural measurements of 1-3 were performed on a Rigaku R-AXIS SPIDER IP diffractometer with graphite monochromated Mo Kα radiation (λ= 0.71073 Å) at 296 K. Crystal data [25] for [Tb(dbm) 3 (14), which indicates that the absolute configurations of 3 can be determined. The crystal data for 1 and 2 are almost the same as the literature [24] .…”
Section: X-ray Crystallography Of Chiral Ln(iii) Complexesmentioning
confidence: 99%
“…Reducing the symmetry of eight-coordinate Eu(III) complexes with a square anti-prism (SAP) geometry by means of reasonable design and synthesis could effectively improve their luminescent properties [9,14] . However, besides SAP polyhedron of eight-coordinate complexes, there are also other stereoisomers [1] , such as triangular dodecahedron (DD), cube, bi-capped triangular prism (TPR) and hexagonal bipyramid (HBP), among which the SAP and DD geometries are particularly the most common ones [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Room-temperature (RT) lasing was obtained with Eu:GaN [8] and Eu:polymer [9] thin films. Recently, 25 at% Eu-doped potassium gadolinium DT, KGd(WO 4 ) 2 , was introduced as novel bulk dielectric material for pulsed room-temperature Eu 3 þ lasing [10].…”
Section: Introductionmentioning
confidence: 99%
“…) show relatively high emission quantum yields (F > 60% in (D 6 )acetone) [13] [14]. The LVF phosphine oxides with attached chemosensing units are expected to be promising ligands for luminescent lanthanide complexes having high emission quantum yields and effective chemosensing properties.…”
mentioning
confidence: 99%
“…The radiative (k r ) and nonradiatve (k nr ) rate constants estimated from the emission lifetimes and the emission quantum yields are also summarized in the Table. The radiative and nonradiative rate constants of [Eu(hfa) 3 In our previous study, we have reported that the coordination geometry of [Eu(hfa) 3 (BIPHEPO)] is characterized as a square-antiprism structure (SAP) with eight coordinating O-atoms (8-SAP), and the two phosphine oxides of the BIPHEPO ligand are located on one square of the 8-SAP (Fig. 3) [14]. The two phosphine oxide sites in the BIPYPO and Me-BIPYPO ligands might also be located on one square of the 8-SAP.…”
mentioning
confidence: 99%